Implementing Animated Short Movie in Teaching Writing Skill of Narrative Tex - Faruk, Ahmad; Ayu Hafidah (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
This research method uses Classroom Action Research (CAR) to identify and solve problems with members' abilities in writing narrative texts. Research hold in English Conversation Club in Darullughih Al-Injiliziyah Dormitory on 14 students of class basic done in two cycles with stages of planning, implementing, observing, and reflecting. This research begins with conducting interviews with teachers who teach writing classes and conducting a pre-test on members first with the number of members. Researchers use qualitative research methods to obtain data. Researchers used three instruments to obtain data, including: observations which included pre-test and post-test, interviews, and documentation